AGE OF FIRST DENTAL VISIT AMONG CHILDREN: REASONS OF THE VISIT AND THE TREATMENT NEEDED (CAHIERS MAGELLANES-NS, 2024)
Background: A child’s first dental visit time is very important for his oral health and future dental behavior. The American Academy of Pediatric Dentistry recommends a first visit by the patient's first birthday or sooner, within six months after the eruption of the first tooth. Early visits can identify early childhood caries (ECC), encourage children to become comfortable with dental dentist, and can also potentially reduce risk of childhood caries. Objective: The purpose of this study was to establish the age at which children have their first dental visit, the reason for the visit, and what the treatments performed during the first appointment. Methods: An online questionnaire was distributed to parents of children with primary or mixed dentition across Saudi Arabia and an observational cross-sectional study was conducted from July to November 2024. Demographic data were collected and the age of first dental visit, reason of visit and treatments received for visit, were queried. SPSS software was used to analysis the data. Results: A total of 624 parents’ participant in which a majority (45.4%) stated that their children first visited the dentist within the age of 3 to 5 years. Routine checkups (39.9%) constituted the prime reason for the visit, pointing increasingly to a trend of preventive care. Over two-thirds received treatment for the first visit and 32.7% received no treatment. Possibly most notably, 62.0% of parents preferred earlier dental visits, and the absence of complaints from the child was the most common reason for delayed visits (56.3%). We found significant relation of the child’s age and gender (p=0.039) and first dental visit age (p=0.0001) using statistical analysis. Conclusion: The findings support the recommendations for early dental visits consistent with preventive care. Despite a growing awareness among parents regarding the significance of early dental care, misconceptions about the necessity of these visits persist. Continued educational efforts are essential to enhance parental understanding and encourage earlier dental consultations, ultimately improving children's oral health outcomes.